EFFECTS OF COMBINED USE OF TROSPIUM CHLORIDE AND MELATONIN ON IN VITRO CONTRACTILITY OF RAT URINARY BLADDER - Onur, R.; Ozcan, M.; Tuygun, U.; Ozan, T.; Ayar, A.; Orhan, I (Wiley-Liss, 2009)
[Abstract Not Available]
39th Annual Meeting of the International-Continence-Society -- SEP 29-OCT 03, 2009 -- San Francisco, CA